Microplastics in soil: A review on methods, occurrence, sources, and potential risk - Yang, Ling; Zhang, Yulan; Kang, Shichang; Wang, Zhaoqing; Wu, Chenxi (The Science of the total environment, 2021)
Microplastic is an emerging contaminant of concern in soil globally due to its widespread and potential risks on the ecological system. Some basic issues such as the occurrence, source, and potential risks of microplastics in the soil are still open questions. These problems arise due to the lack of systematic and comprehensive analysis of microplastic in soils. Therefore, we comprehensively reviewed the current status of knowledge on microplastics in soil on detection, occurrence, characterization, source, and potential risk. Our review suggests that microplastics are ubiquitous in soil matrices globally. However, the research progress of microplastics in the soil is restricted by inherent technological inconsistencies and difficulties in analyzing particles in complex matrices, and studies on the occurrence and distribution of microplastics in soil environments remain very scarce, especially in Africa, South America, and Oceania. The consistency of the characteristics and composition of the microplastics in the aquatic environment and soil demonstrate they may share sources and exchange microplastics. Wide and varied sources of microplastic are constantly filling the soil, which causes the accumulation of microplastics in the soil. Studies on the effects and potential risks of microplastics in soil ecosystems are also reviewed. Limited research has shown that the combination and interaction of microplastics with contaminants they absorbed may affect soil health and function, and even migration along the food chain. The occurrence and impact of microplastic on the soil depend on the morphology, chemical components, and natural factors. We conclude that large research gaps exist in the quantification and estimation of regional emissions of microplastics in soil, factors affecting the concentration of microplastics, and microplastic disguising as soil carbon storage, which need more effort. [Display omitted] •Microplastics are ubiquitous in the soil environment.•The monitoring data of microplastics are insufficient.•Soil and other environmental matrices share and exchange microplastics.•The quantification and estimation of microplastics in soil are imperative.•Microplastics pose potential impacts on soil ecosystems and human food chains.